Burning the candle at both ends: motivations for non-medical prescription stimulant use in the American workplace. (4th July 2019) - Sales, Paloma; Murphy, Fiona; Murphy, Sheigla; Lau, Nicholas
Abstract: Studies indicate prescription stimulant use for cognitive performance enhancement is normalized, contributing to increases in non-medical prescription stimulant use (NPSU) through peer recommendations and drug diversion. NPSU may follow users beyond their academic years to the workforce with some initiating use later in adulthood. Aims : Examine findings from a San Francisco Bay Area National Institute on Drug Abuse funded research project. Explore motivations to initiate and continue NPSU focusing on San Francisco Bay Area adults in the workforce. Analyze motivations for use and use practices within the American sociocultural context. We also examine consequences of use, including falling into the 'Adderall trap' – a cycle of using to perform, sleeplessness, then using again to wake up and perform. Methods : 67 in-depth interviews analyzed using Grounded Theory methods. Findings : Increased availability combined with pressure to perform and compete at work, facilitated decisions to initiate and continue use. Some also used recreationally to mitigate the effects of alcohol and prolong a night out. Conclusions : Cultural factors such as the pressure to perform in a society as the US valuing hard work, competition, and success motivate NPSU. In these cases, NPSU is not necessarily considered to be deviant, but rather following conventional values.